Multichannel read-out for arrays of metallic magnetic calorimeters. (2nd August 2021) - Mantegazzini, F.; Allgeier, S.; Barth, A.; Enss, C.; Ferring-Siebert, A.; Fleischmann, A.; Gastaldo, L.; Hammann, R.; Hengstler, D.; Kempf, S.; Richter, D.; Schulz, D.; et al.
Abstract: Metallic magnetic micro-calorimeters (MMCs) operated at millikelvin temperature offer the possibility to achieve eV-scale energy resolution with high stopping power for X-rays and massive particles in an energy range up to several tens of keV. This motivates their use in a wide range of applications in fields as particle physics, atomic and molecular physics. Present detector systems consist of MMC arrays read out by 32 two-stage SQUID read-out channels. In contrast to the design of the detector array and consequently the design of the front-end SQUIDs, which need to be optimised for the physics case and the particles to be detected in a given experiment, the read-out chain can be standardised. We present our new standardised 32-channel parallel read-out for the operation of MMC arrays to be operated in a dilution refrigerator. The read-out system consists of a detector module, whose design depends on the particular application, an amplifier module, ribbon cables from room temperature to the millikelvin platform and a data acquisition system. In particular, we describe the realisation of the read-out system prepared for the ECHo-1k experiment for the operation of two 64-pixel arrays. The same read-out concept is also used for the maXs detector systems, developed for the study of the de-excitation of highly charged heavy ions by X-rays, as well as for the MOCCA system, developed for the energy and position sensitive detection of neutral molecular fragments for the study of fragmentation when molecular ions recombine with electrons. The choice of standard modular components for the operation of 32-channel MMC arrays offer the flexibility to upgrade detector modules without the need of any changes in the read-out system and the possibility to individually exchange parts in case of damages or failures.